Thing as a Standard of Colour: Formation of Non-Basic Colour Names in Russian Language - L. Zhang (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The analysis of secondary colour nominations attributing a shade by means of attraction of real images is carried out. The material for the study was “The Unique Reference with Parameters (RGB, HSV, CMYK, hex) and Names of about 1,000 Colours” on the web-site http://tinyurl.ru/services/colour/list. Names of shades of colour are characterized from the point of view of their structural characteristics and motivational characteristics. It is found that colour names with the subject reference may be single-word units, and may provide a simple and comprehensive phrases, the structure of which is not always a colour symbol or a reference to a colour of any object. It is shown that the studied colour nominations are often derived from phytonyms, zoonyms, hydronyms and other words naming objects of living and inanimate nature. It is noted that some of the non-basic colour names are derived from nouns that name personalities, geographical objects, organizations, etc. Usually such colour names are focused on attracting the attention of an educated recipient of speech. The analysis of the material confirms the opinion of other researchers of colour nominations: they believe that colour naming is often based on metaphorical and metonymic transfer of a meaning.